Rainbow Jordan - Childress, Alice (New York : Coward, McCann & Geoghegan, 1982)
Her mother, her foster guardian, and 14-year-old Rainbow comment on the state of things as she prepares to return to a foster home for yet another stay.
Keywords: Foster home care -- Fiction; Mothers and daughters -- Fiction; African Americans -- Fiction